Pengaruh Inflasi, Penagihan Pajak dan Penyuluhan Pajak terhadap Penerimaan Pajak Penghasilan - Putri Nadia; Rayna Kartika (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study aims to examine the effect of inflation, tax collection, and tax education on income tax revenue. This study uses report data documented from the Tampan subdistrict tax office in Pekanbaru and the Central Statistics Agency of Pekanbaru in the form of inflation data, billing activities, and tax counseling for 3 years (January 2017 - December 2019). Data were analyzed using Multiple Regression analysis. The results showed that inflation and tax counseling variables significantly influence income tax revenue. On the other hand, the tax collection variable has no significant effect on income tax revenue. This finding underlines the collection of income tax does not have a significant effect on income tax revenue is due to tax collection carried out on all people who have tax arrears. As a contribution that in the issuance of Tax Collection Letter (STP), the tax authorities can focus the issuance of STP to taxpayers who have large amounts of arrears, so that income tax revenue can increase faster. because more and more STPs issued to prove that tax collection activities may not be able to run effectively.